Marketing faculty of Bucharest Economic Studies University: historic landmarks, present and future developments - Călin Petrică Vegheş; Ionel Dumitru; Ioana Cecilia Popescu; Mihai Cristian Orzan (Amfiteatru Economic Journal, 2013)
This paper aims to present the main events that left their mark on the history and evolution of the Marketing Faculty of Bucharest Economic Studies University, an academic body that this will mark its 10th anniversary this fall. As the only school dedicated exclusively to the study of marketing in Romania, as well as one of the few exclusively marketing schools in Europe, the history of the Marketing Department and, subsequently, of the Marketing Faculty overlaps in the last four decades with that of Romanian marketing higher education, as well as with the graduate transformation of Romania's economy to a post-industrial, information-based and customer centric economy. Part of Economic Sciences domain, marketing contains a set of concepts, tools, methods and techniques through which the organization, irrespective of its profile, analyzes the environment where it lives (marketing research), sets goals and strategies to be achieved (strategic marketing planning), design and execute operational activities (marketing programs) in order to maximize profits and to satisfy customer's and society's needs at the required level. Marketing as a strategic and operational area, captures the interest of Romanian managers and specialists of international organizations, being a source of competitive advantage and positioning of the company and its portfolio brands, in the mind and soul of current and potential customers.
Keywords: M31; 330; Marketing; History; Evolution; Romanian Economy; Higher Education